Pomen Milka Matičetovega za zahodne Slovence - Miklavčič-Brezigar, Inga (Traditiones (Ljubljana), 1999)
The article describes the importance of ethnologist and folklorist Milko Matičetov for Primorsko, the area of the western Slovene ethnic territory. It is based on Dr. Matičetov's early works, synthetic ethnological and folkloristic reviews of western Slovenes, and on comparing elements from the area's spiritual folk culture to those of neighboring nations
Keywords: Matičetov, Milko, 1919-; ethnology; etnologija; Slovenci; Slovenes